Editorial - Preudhikulpradab, Sirichai (ABAC ODI JOURNAL Vision. Action. Outcome, 2021)
Editorial Sirichai Preudhikulpradab, Ph.D., Ed.D. Program Director, Master of Management and Organization Development Assumption University, Bangkok, Thailand The ABAC ODI Journal issue has six articles that stem from research-based works by graduate students, organization practitioners, and academia. The contributing authors are international and domestic scholars comprising Cambodia, China, Myanmar, the Philippines, and Thailand. This issue also includes the book review of John Rawls His Theory of Justice Thomas Pogge. The first article, titled “Designing a Prototype Coaching Model Based on Emotional Intelligence and Job Performance: A Case Study of Global Technology Group Company, Myanmar.” by Min Swe Hlaing and Maria Socorro C.L. Fernando. This article employs mixed-method research, aiming at examining the influence of independent variables (e.g., self-awareness, self-management, social management, and relationship management) on job performance as a dependent variable, and lastly, proposing a coaching model. The second article, titled “Designing A Framework and Strategies to Enhance Individual Innovative Work Behavior: A Case of a Non-Profit in Phnom Penh, Cambodia.” by Sonika Seng and Maria Socorro C. L. Fernando. The article employs needs assessment research to identify the priority needs of five variables for Organization development interventions identification. The research site is a Non-Profit Organization in Cambodia. The third article, titled “Strategies to Improve Employees’ Work Efficiency in one branch of ABC Thai Restaurant.” by ShuYue Zheng and Maria Socorro C. L. Fernando. This article employs mixed-method research to identify the priority needs index for additional improvement programs identification for employee’s work efficiency. The research site is in Bangkok, Thailand. The fourth article, titled “Key Developmental Opportunities for Long-Term Organization Development of G Commercial Bank, China: A Mixed-Method Research.” by YuJie Wu and Sirichai Preudhikulpradab. The article employs needs assessment research to identify priority needs index and propose long-term Organization development interventions. The research site is in China. The fifth article, titled “A Roadmap for Future Development of Leadership Competencies of ABC Non-Profit Organization, Thailand and Myanmar.” by Nang Bawk and Sirichai Preudhikulpradab. The article employs mixed-method research, aiming to examine the gaps between the current and expected leadership competencies and develop a roadmap for future development of the organization’s leadership competencies. The research site is in Thailand and Myanmar. The sixth article, titled “Organizational Effectiveness Enhancement Through the Lens of Lifelong Learning.” by Sanhakot Vithayaporn. The article employs a meta-analysis research technique to examine, conceptualize and identify the commonalities of the confirmed factors impacting organizational effectiveness based on different findings of the twenty research-based articles. In summary, five out of sixth articles are organization case studies whereby the researchers as the authors employ mixed-method research to confirm key research findings and propose Organization Development Interventions. One out of six articles employs meta-analysis research to conceptualize common factors impacting organizational effectiveness. We hope the readers find the current issue of the ABAC ODI journal provides you with interesting findings and practical insights on different types of research methodologies and choices of Organization Development interventions drawn from the analyzed data.